Specific inhibitor of Smad3 (SIS3) alleviated submandibular gland fibrosis and dysfunction after dominant duct ligation in mice - Honglin Li; Guanru Wang; Minqi Hu; Runnan Dai; Chunjie Li; Yubin Cao (Elsevier, 2023)
Background/purpose: Chronic obstructive sialadenitis (COS) is a condition that severely reduced patients' quality of life. This study aimed to analyze the effects of SIS3, a specific inhibitor of small mothers against decapentaplegic 3 (SMAD3), on the submandibular gland (SMG) dysfunction, fibrosis, and inflammation. Materials and methods: The dominant duct in the SMG was ligated in mice, followed by intraperitoneal injection of SIS3 (2 mg/kg/day) or Dimethyl sulfoxide (DMSO) saline for 7 days. In the sham group, this duct was surgically identified but not ligated. Saliva flow, histological structure, fibrosis, Transforming growth factor-β1 (TGF-β)/SMAD3 signaling, and inflammatory cytokines, were analyzed. Results: SIS3 rescued ligation-induced SMG dysfunction and improved the saliva flow rate compared to DMSO. SIS3 alleviated acinar atrophy and ductal dilation and maintained the morphology of the basal membrane. SIS3 reduces interlobular and intralobular fibrosis and collagen deposition. We observed reduced SMAD3 phosphorylation and TGF-β expression. The SIS3 group showed downregulation of np_5318 and miR-21 and upregulation of miR-29 b compared to the DMSO group. Moreover, SIS3 controlled the inflammatory cytokine release, including interleukin-6 and interleukin-1β. Conclusion: SIS3 protected duct-ligated SMGs against fibrosis and dysfunction by inhibiting the TGF-β/SMAD3 signaling and inflammatory cytokine expression. SIS3 may serve as a promising treatment for chronic obstructive sialadenitis.